Porosity and thickness effect of Pd–Cu–Si metallic glasses on electrocatalytic hydrogen production and storage. (15th November 2021) - Sarac, B.; Karazehir, T.; Yüce, E.; Mühlbacher, M.; Sarac, A.S.; Eckert, J.
Graphical abstract: Highlights: β c _ m i n  = 42 mV dec –1 observed for t  = 10 nm coating on d  = 2 µm with s  = 4.2 µm. High average capacitance parameter of ∼ 0.001 S s n cm −2 observed for the same sample. η 10 is down to –138 mV vs. RHE for t  = 50 nm, d  = 2 µm and s  = 4.2 µm. Δ Q : 397–554 µC cm −2 for t  = 250 nm and Δ Q : –678 - –1152 µC cm −2 t  = 10 nm series. Slight peak of Pd (Pd 2+ ) at ∼ 337 eV correspond to PdO x formation on the surface. Abstract: This contribution places emphasis on tuning pore architecture and film thickness of mesoporous Pd–Cu–Si thin films sputtered on Si/SiO2 substrates for enhanced electrocatalytic and hydrogen sorption/desorption activity and their comparison with the state-of-the-art thin film electrocatalysts. Small Tafel slope of 43 mV dec –1 for 1250 nm thick coating on 2 µm diameter pores with 4.2 µm interspacing electrocatalyst with comparable hydrogen overpotentials to the literature suggests its use for standard fuel cells. The largest hydrogen sorption has been attained for the 250 nm thick electrocatalyst on 5 µm pore diameter with 12 µm interspacing (2189 µC cm −2 per CV cycle), making it possible for rapid storage systems. Moreover, the charge transfer resistance described by an equivalent circuit model has an excellent correlation with Tafel slopes. Along with its very low Tafel slope of 42 mV dec –1 10 nm thick electrocatalyst on 2 µm diameter pores with 4.2 µm interspacing has the highest capacitive response of ∼ 0.001 S s n cm −2 and is promising to be used as a nano-charger and hydrogen sensor. The findings of Si/SiO2 supported mesoporous Pd-based metallic glass (MG) assemblies suggest a similar design applicability for crystalline systems and other MG types.